Pregnancy at the Cesarean Section Scar: Successful Management and Review of Current Literature - Singh, Pratibha; Raikar, Sunil; Yadav, Garima; Gothwal, Meenakshi; Ghuman, Navdeep (Annals of the National Academy of Medical Sciences (India), 2020)
When implantation of the early embryo occurs at the scar of previous cesarean, it is called cesarean scar pregnancy. Though in uterus, it behaves like an ectopic pregnancy with risk of rupture and hemoperitoneum. A 37-year-old woman came with missed period and vague abdominal discomfort; she had a positive pregnancy test. She had previous two cesarean sections. The last cesarean section was 12 years ago and the patient was not using any contraception. Her ultrasonography (USG) was inconclusive; β human chorionic gonadotropin was 2,980 mIU/mL. Her repeat USG showed a hypoechoic area at the cesarean scar site, behind the reflection of bladder, separated from bladder by a thin layer of myometrium. She was counseled regarding the management options and prognosis. She was managed with two doses of injection. Methotrexate on day 1 and day 4. β human chorionic gonadotropin was repeated until it was close to normal. USG was also repeated. Cesarean scar pregnancy can be managed by many ways; the one most suitable to the patient with least side effects should be adopted, after adequate counseling of the patient.
Keywords: cesarean scar pregnancy; scar site pregnancy; ectopic pregnancy